EGG QUALITY OF SELECTED ACEH NATIVE CHICKENS FED ON THE DIETS COMPOSED OF Indigofera sp. MEAL BASED ON FEED FERMENTATION AS PARTLY SUBSTITUTION OF COMMERCIAL DIET - Yaman, Muhammad Aman; Zulfan, Zulfan (Jurnal Kedokteran Hewan, 2019)
The objective of this study was to determine the effect of inclusion of fermented feed consisted of 15% Indigofera sp. + 40% rice bran + 25% corn bran + 20% soybean meal as partial substitution of commercial diet on the egg quality of selected Aceh native (SAN) chickens. As many as 48 SAN pullets were used in this study. The study was performed in a completely randomized design, consisted of 4 treatments and 4 replications. Each replication was an experimental unit consisted of three chickens. The results of study indicated that inclusion of up to 15% fermented feed which was composed of 15% Indigofera sp. + 40% rice bran + 25% corn bran + 20% soybean meal as substitution of commercial layer diet significantly (P0.01) improved yolk index without adverse effect on albumen and eggshell quality of SAN chickens. As conclution, substitution of fermented feed contained 15% indigofera may improve the egg quality of SAN chickens.